OV329, a novel highly potent γ‐aminobutyric acid aminotransferase inactivator, induces pronounced anticonvulsant effects in the pentylenetetrazole seizure threshold test and in amygdala‐kindled rats. (7th October 2021) - Feja, Malte; Meller, Sebastian; Deking, Lillian S.; Kaczmarek, Edith; During, Matthew J.; Silverman, Richard B.; Gernert, Manuela
Summary: Objective: An attractive target to interfere with epileptic brain hyperexcitability is the enhancement of γ‐aminobutyric acidergic (GABAergic) inhibition by inactivation of the GABA‐metabolizing enzyme GABA aminotransferase (GABA‐AT). GABA‐AT inactivators were designed to control seizures by raising brain GABA levels. OV329, a novel drug candidate for the treatment of epilepsy and addiction, has been shown in vitro to be substantially more potent as a GABA‐AT inactivator than vigabatrin, an antiseizure drug approved as an add‐on therapy for adult patients with refractory complex partial seizures and monotherapy for pediatric patients with infantile spasms. Thus, we hypothesized that OV329 should produce pronounced anticonvulsant effects in two different rat seizure models. Methods: We therefore examined the effects of OV329 (5, 20, and 40 mg/kg ip) on the seizure threshold of female Wistar Unilever rats, using the timed intravenous pentylenetetrazole (ivPTZ) seizure threshold model as a seizure test particularly sensitive to GABA‐potentiating manipulations, and amygdala‐kindled rats as a model of difficult‐to‐treat temporal lobe epilepsy. Results: GABA‐AT inactivation by OV329 clearly increased the threshold of both ivPTZ‐induced and amygdala‐kindled seizures. OV329 further showed a 30‐fold greater anticonvulsant potency on ivPTZ‐induced myoclonic jerks and clonic seizures compared to vigabatrin investigated previously. Notably, all rats were responsive to OV329 in both seizure models. Significance: These results reveal an anticonvulsant profile of OV329 that appears to be superior in both potency and efficacy to vigabatrin and highlight OV329 as a highly promising candidate for the treatment of seizures and pharmacoresistant epilepsies.